Influence of E-Wom, Innovation, E-Trust, and Website Attractiveness on Purchase Decision - Solikhah, EfA Wakhidatus; Garad, Askar (Jurnal Manajemen Teknologi, 2024)
Abstract. This research explores the impact of product innovation, website attractiveness, electronic word of mouth (e-WOM), and electronic trust (e-trust) on consumer purchasing decisions in the context of online transactions. In this explanatory quantitative study, the sample consists of 142 consumers who made online purchases through company website accounts. Data collection was conducted using questionnaires, and analysis was performed through the Structural Equation Modeling (SEM) approach with the assistance of SPSS software. The research results indicate that all variables, namely product innovation, website attractiveness, e-WOM, and e-trust, significantly and positively influence consumer purchasing decisions. These findings provide in-depth insights into the factors affecting consumer preferences in online purchases, with key roles played by e-WOM, online reputation, online social interaction, website attractiveness, and electronic trust. Practical implications emphasize the need for companies to focus on the development of attractive websites, the management of e-WOM, and the establishment of an online trust to enhance consumer purchasing decisions online. In conclusion, product innovation is also a crucial factor in capturing consumer attention in the competitive online environment. By implementing these findings, companies can design more effective marketing strategies, enhance online attractiveness, build consumer trust, and ultimately improve consumer purchasing decisions. Keywords: E-WoM, e-trust, web attractiveness, inovasi, dan purchase decision    Abstrak. Penelitian ini mengeksplorasi dampak inovasi produk, daya tarik situs web (web attractiveness), electronic word of mouth (e-WOM), dan electronic trust (e-trust) terhadap keputusan pembelian konsumen dalam konteks transaksi online. Dalam studi kuantitatif eksplanatif ini, sampel terdiri dari 142 konsumen yang melakukan pembelian online melalui akun situs web perusahaan. Pengumpulan data dilakukan menggunakan kuesioner, dan analisis dilakukan melalui pendekatan Structural Equation Modeling (SEM) dengan bantuan perangkat lunak SPSS. Hasil penelitian menunjukkan bahwa semua variabel, yakni inovasi produk, daya tarik situs web, e-WOM, dan e-trust, secara positif dan signifikan memengaruhi keputusan pembelian konsumen. Temuan ini memberikan wawasan mendalam tentang faktor-faktor yang memengaruhi preferensi konsumen dalam pembelian online, dengan peran kunci dari e-WOM, reputasi online, interaksi sosial online, daya tarik situs web, dan kepercayaan elektronik. Implikasi praktisnya menekankan perlunya fokus perusahaan pada pengembangan situs web yang menarik, manajemen e-WOM, dan pembangunan kepercayaan online untuk meningkatkan keputusan pembelian konsumen secara online. Kesimpulannya, inovasi produk juga menjadi faktor penting dalam menarik perhatian konsumen dalam lingkungan online yang kompetitif. Dengan menerapkan temuan ini, perusahaan dapat merancang strategi pemasaran yang lebih efektif, meningkatkan daya tarik online, membangun kepercayaan konsumen, dan akhirnya, meningkatkan keputusan pembelian konsumen.  Kata kunci: E-WoM, e-trust, web attractiveness, inovasi, dan purchase decision